(untitled) (Third Sector Social Economic Review, 2022)
The coronavirus (COVID-19) pandemic that broke out in Wuhan, China, in late 2019 has affected many areas of life, particularly health, social life, economy, education, professional life, friendship and family relations. While countries resorted to social closure (shut-down) and social isolation measures, families and individuals have also been affected by this situation and changes in behavior have been experienced. Throughout this period, family members who could not go to school or their workplaces and had to stay at home had to lead a family life outside of their usual routine. In this context, this study aimed to reveal the impact of the COVID-19 pandemic on family relations from the perspective of university students. The qualitative method was adopted for the purposes of the study. The snowball sampling method, which is one of the purposeful sampling techniques, was used; thereby, in-depth one-to-one interviews were conducted with a total of 16 students studying in different departments of a private university in Turkey while living with their families. Semi-structured interview protocol was used as a data collection tool. All the interviews were conducted in person. The results of the study revealed that the COVID-19 pandemic has negatively affected family relationships. Accordingly, it was concluded that the pandemic caused verbal, physical and economic violence among family members, the lifestyle of whole family has changed, the family has experienced economic problems, domestic responsibilities at home have mostly been assumed by mothers and daughters, the time spent by family members over the internet and in front of TV has been prolonged, sleeping and eating habits have been adversely affected.